Direct healthcare costs and resource consumption after acute coronary syndrome: a real-life analysis of an Italian subpopulation. (29th August 2020) - Roggeri, Daniela P; Roggeri, Alessandro; Rossi, Elisa; Cinconze, Elisa; De Rosa, Marisa; Maggioni, Aldo P; ,
Abstract: Background: Acute coronary syndrome (ACS) is the most common cause of morbidity and mortality in Italy and worldwide. Aim of this study was to evaluate the average annual direct healthcare costs for the treatment of patients with a recent hospitalization for ACS. Design and methods: The direct medical costs of patients with a first ACS hospitalization (index event) in the period from 1 January 2008 to 31 December 2008 were estimated for a 1-year follow-up period. The resource consumption was measured in terms of: reimbursed drugs, diagnostic procedures, outpatient visits, and hospitalizations. The analysis was performed from the Italian National Health Service perspective. Results: A total of 2, 758, 872 subjects were observed, 7082 (35.8% women) of whom being hospitalized for ACS during the accrual period (2.6‰). Among patients with ACS, 60% were medically treated, 33.1% were treated with percutaneous coronary intervention (PCI), and 6.9% died during the index hospitalization. Dual antiplatelet treatment (ASA plus clopidogrel) was prescribed in 25.9% of the medically treated ACS patients and in 70.1% of the ACS patients treated with PCI. The average yearly cost per patient for the total ACS population was 11, 464€/year (drugs 1304€; hospitalizations 9655€; diagnostic and outpatient visits 505€). The average annual cost was 10, 862€ for medically treated patients and 14, 111€ for patients treated with PCI. Patients who died of cardiovascular events during follow up had an average cost of 16, 231€/patient. Conclusions: Patients with ACS had higher direct healthcare costs, their management and rehospitalizations being the main cost drivers.